2016
DOI: 10.1111/nmo.12851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D on gastrointestinal symptoms and health‐related quality of life in irritable bowel syndrome patients: a randomized double‐blind clinical trial

Abstract: Vitamin D seems to be an effective and safe option to improve QoL and symptoms of IBS. ClinicalTrials.gov (NCT02579902).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 47 publications
6
77
3
2
Order By: Relevance
“…This is in accordance with other studies in elderly community‐living participants and in heart failure patients . However, other studies have reported improvement in quality of life in patients with irritable bowel syndrome as well as in patients with Crohn's disease, the latter in an uncontrolled trial …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with other studies in elderly community‐living participants and in heart failure patients . However, other studies have reported improvement in quality of life in patients with irritable bowel syndrome as well as in patients with Crohn's disease, the latter in an uncontrolled trial …”
Section: Discussionsupporting
confidence: 92%
“…This should be highly relevant in the context of the possible pleiotropic effects of vitamin D, where quality of life could be considered a composite end‐point integrating various health effects of vitamin D. Observational studies have reported positive associations between serum 25(OH)D levels and quality of life . The results from intervention studies are, however, conflicting …”
Section: Introductionmentioning
confidence: 99%
“…In fact, vitamin D has been proposed as a potential treatment for IBS. 38,39 Due to the relative abundance of vitamin D responsive elements (VDREs) in hundreds of vitamin D regulated genes throughout the genome, 40 we postulated that expression of some IBS candidate biomarker genes may be influenced by the presence of the active hormonal metabolite of vitamin D, 1,25-dihydroxyvitamin D 3 (1,25D). 41 The manner in which this potential regulation occurs and the specific genes involved in IBS pathophysiology may suggest possible new approaches to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ­vitamin D deficiency is common among IBS patients [11, 36]. ­Indeed, as in a previous case report [10] and according to a recent randomized control trial [37] study, vitamin D supplementation has a beneficial effect on the IBS symptoms; currently vitamin D is considered to have potential benefits in the treatment of IBS [10]. …”
Section: Discussionmentioning
confidence: 68%